Reverse Design of Conjugate Cam Mechanism based on Polynomial Fitting Method - Zhang Shuanglin; Ge Zhenghao; Zhang Xingyu; Li Chengping (Jixie chuandong)
A method of reverse design of conjugate cam is introduced. By using Pro / E with the contour surface data of CAM,the 3- D model is built and kinematics simulation analysis is carried out,the displacement,velocity and acceleration curves of the following mechanism are got before the reverse. Then,by using the polynomial law of motion to fit the original one after getting the parameters with the motion curves after dimensionless processing. Finally,comparing the kinematics simulation after the reverse with the former one. The transmission accuracy and work efficiency of cam are proved to be greatly improved through the simulation and trial- manufacture.